2021
DOI: 10.1016/j.jopan.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Education, Competence, and Role of the Nurse Working in the PACU: An International Survey

Abstract: The aim of this research project was to describe the education, competence, and role of nurses working in the postanesthesia care unit (PACU) in 11 countries having an established perianesthesia specialty nursing organization and membership on the International Collaboration of PeriAnaesthesia Nurses, Inc (ICPAN) Global Advisory Council (GAC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…It can also form guidelines for skill acquisition by nursing students and nurses at lower competence levels. As there is no education specifically for nurses working in PACUs in Sweden, the present results together with those of two other studies by the same authors [12,13] could form the basis for developing education for PACU nurses in Sweden.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It can also form guidelines for skill acquisition by nursing students and nurses at lower competence levels. As there is no education specifically for nurses working in PACUs in Sweden, the present results together with those of two other studies by the same authors [12,13] could form the basis for developing education for PACU nurses in Sweden.…”
Section: Discussionsupporting
confidence: 63%
“…To enable safe and successful recovery for patients who have undergone surgery, nurses need competence in postoperative care [10,11]. However, there is no consensus regarding the competence or education needed to provide safe, highquality patient care in post-anaesthesia care units (PACU) [12,13]. This lack of consensus has been raised and discussed by the ICPAN, International Collaboration of PeriAnesthesia Nurses board and its members and is an area that needs further development and collaboration to strengthen nursing in the PACU [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Inspiration for the web‐based survey used here came from a survey that our research group developed for an international study describing the education, competence and role of RNs working in PACUs in 11 Western countries (6). The questions concerned phase‐1 and phase‐2 recovery, where phase 2 refers to day surgery only.…”
Section: Methodsmentioning
confidence: 99%
“…Specialized nursing care during postoperative recovery in the hospital is rarely described in the literature. Few countries have formal education for nurses working in PACUs (6). Poole reported that nurses with different levels of education (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We are fortunate to have the richness of information that comes from a global community who are interested in the same preanesthesia, postanesthesia, sedation, and quality issues that we are. Consider the research conducted by Dahlberg and others 4 that focused on competencies of perianesthesia nurses around the globe.…”
mentioning
confidence: 99%